A new species of deeper dwelling West Pacific cardinalfish (Percomorpha: Apogonidae) with a redescription of Ostorhinchus atrogaster - Fraser, Thomas H. (Zootaxa, 2012)
A new species of cardinalfish is described from Palau. A deep-water species from 72 meters on a steep drop off is unlikelyto be collected often. This slender species may belong with a group of deeper dwelling cardinalfishes. Fresh post-mortemspecimens differ in color pattern from other translucent Ostorhinchus in having a faint yellow midline stripe ending in adiffuse scattering of melanophores forming a basicaudal spot, a yellowish nape stripe above lateral-line scales reaching tonear mid-base of the second dorsal fin, melanophores forming a short band along the side of the abdomen from near theanus to below the pectoral-fin base, lower lip and snout dusky. Ostorhinchus atrogaster is redescribed from the type ma-terial and differs from the new species in dentition on the premaxilla and dentary and having a silvery line above the lateral line to the base of the caudal fin.